Perception of vocational colleges academic staffs’ on the importance and readiness to collaborate with industry - Faizatul Ashikin Ramli,; Nur Husna Abd Wahid, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The partnership between the industrial sector and technical vocational institutions is a networking towards achieving common goals and provide mutual benefits to both parties. A strong collaboration between vocational colleges and industries is important to bring the country economic growth towards the sustainability of technical and vocational education (TVET) in Malaysia. Collaborations conducted between vocational colleges and industries will create a positive impact through the sharing of additional knowledge and consensus to reduce the mismatch of industrial needs among graduates. However, there is doubt on capability that collaboration can benefits each other between education institution and industry where academics and industry do not understand each other or not capable or ready to collaborate. There is the issues that understanding the readiness of individuals from both sides to engaging the collaboration. Therefore the purpose of this paper is to indentify the importance of vocational colleges - industries collaboration element perceived by vocational colleges academic staff ; and indentify the readiness of vocational colleges - industries collaboration element perceived by vocational colleges academic staff. The data of this study were obtained through questionnaires and analysed using SPSS (Statistical Package for Social Science). Researchers used the entire population 195 vocational academic staffs as a study sample. The six elements of collaboration identified are a) placement in the industry b) curriculum c) added value c) support d) facilities and e) training. The findings of the study found that the majority of vocational academic staffs showed perception of important and ready to implement the element of collaboration with industry. Thus it showed that all these element is importand and ready to implement to collaborate with the industry towards sustainability of vocational colleges.